2010
DOI: 10.2341/09-185-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adhesives and Thermocycling on the Shear Bond Strength of a Nano-Composite to Coronal and Root Dentin

Abstract: SUMMARYObjectives: To evaluate the effects of "etch & rinse" vs "self-etch" adhesives and thermocycling on the shear bond strength (SBS) of a nano-composite to coronal and root dentin. Materials and Methods: Fifty-six extracted human molars were mounted and ground to expose coronal and root dentin surfaces and were randomly divided into two groups according to adhesive system: SE-a two-step self-etch adhesive (Adper SE Plus, 3M ESPE) and ER-an etch & rinse adhesive (Adper Single Bond 2, 3M ESPE). The adhesives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
32
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 27 publications
6
32
0
2
Order By: Relevance
“…Comparing the two studies several differences could be observed: the adhesive system, the duration of water storage, thermocycling and the adhesive area. A more recent study found very similar results to the present study for FSXT (in a range from 11.01 ± 4.56 MPa to 15.36 ± 6.00 MPa) [33], although differing in a few parameters, like other adhesives and no thermocycling. A review [34] demonstrated the diversity of the results of SBS tests, ranging from 3–61 MPa.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Comparing the two studies several differences could be observed: the adhesive system, the duration of water storage, thermocycling and the adhesive area. A more recent study found very similar results to the present study for FSXT (in a range from 11.01 ± 4.56 MPa to 15.36 ± 6.00 MPa) [33], although differing in a few parameters, like other adhesives and no thermocycling. A review [34] demonstrated the diversity of the results of SBS tests, ranging from 3–61 MPa.…”
Section: Discussionsupporting
confidence: 87%
“…The lack of standardization is one of the problems with SBS tests. Simple testing parameters, like crosshead speed [35,36], aging process [33,37] or storage conditions of the natural teeth [38,39,40], have demonstrable influence on the results. Another deficit emphasized by Scherrer [34] was the fracture pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding bond strength studies, SE has resulted in statistically higher dentin bond strengths than EB. 30 The bond strengths obtained with SE are not affected by thermal fatigue when bonded to coronal dentin 31 ; this may be a result of minimal residual water left entrapped within the dentin-adhesive interface.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, a sharp increase in adhesion strength after 6,000 cycles was observed in the group-BM. This could be attributed to release of stresses generated during the polymerization contraction of resin composite 20) . Moreover, the cross-linking silane (BTSE) together with the functional silane (ACPS) might improve bonding by forming a 3D siloxane film that contributed to bonding between the dissimilar materials.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the increase in adhesion strength values in group-BM, a sharp decline in the adhesion strength values in all other experimental groups is in accordance with some previous studies 1,10,21,22) . Nevertheless, thermo-cycling is a widely used and accepted rapid, accelerated aging method used in laboratories, in addition to the shear bond strength test, regardless of their undisputable limitations 20) . The experimental silanes showed promising results with Multilink ® Speed resin composite cement in both baseline and thermo-cycled study groups.…”
Section: Discussionmentioning
confidence: 99%